Pesquisa de Polymavirus-BK em transplantes renais: incidência e correlação com parâmetros clínicos e laboratoriais - Svicero, Bianca Silva [UNIFESP] (2010)
Introduction: The BK virus (BKV) belongs to the Polyomaviridae family, is a non enveloped virus with double-stranded DNA, may be associated with hemorrhagic cystitis, ureteral stenosis, and in some cases, cancer. The polyomaviruses are found in about 80% of the general population, however its clinical manifestations are rare and limited to individuals with weakened immune system. The BKV is a virus with the potential to establish latency and reactivate. Asymptomatic reactivation and low level of replication are observed in approximately 5% of the healthy population. In the patients of renal transplant. Reactivation becomes relevant, since 10-40% of patients with BKV active infection can progress to graft loss. The diagnosis of BKV infection can be accomplished by “decoy” cells in urinary sediment and / or viral load evaluation by polymerase chain reaction in Real Time (qPCR). Treatment is not defined by antiviral drugs but by reducing the dose of immunosuppressive drugs. Objectives: The aim of this study was to standardize Real Time PCR to estimate the BKV viral load in plasma and urine and the presence of “decoy” cells in urine of patients undergoing renal transplantation in the period between november/2008 and may/2010, since pre transplant until 12 months after transplantation. Analysis of epidemiological aspects related to infection and the correlation with the course of the disease were evaluated as well. Methods: Analysis of urine sediment by Papanicolaou staining for the presence of "decoy" cells by electron microscopy. For standardization of Real-Time PCR in plasma and urine a commercial BKV DNA with a viral load set at 1.6 x105cópias / mL was used for the construction of standard curve; betaglobin was used as an internal control. Based in the techinique publishe in 2004 by Randhawa and colleagues. Results: The study included 81 patients followed prospectively over 12 months, where 70.3% were male with median age of 39 years at the time of transplantation. The urine cytology provided a positive result in 1.6% of the samples. The standard curve was performed by five serial dilutions of positive control (1-104), the slope of the curve was -3.60, the Pearson correlation coefficient was r2 = 0.99 and efficiency of the reaction was 91 6%. Plasma samples showed variations in viral load, 39.1% from the 1.08 x104 9.51 x104 copies / mL and 26.3% with viral load greater than or equal to 1x105 copies / mL and 34.6% with viral load below 1x104 copies / mL. We demonstrated an incidence of 29 cases by 1000 patients. The clinical features did not correlate with laboratory findings found, since there was no description of symptoms related to infection with BKV in patients supposedly with viral load indicative of infection during the 12 months analyzed. Conclusions: The standardization of real-time PCR was achieved and can be compared with previous studies..We didn’t consider the PCR results indicative of disease because a reanl biopsy was not performed. The result of decoy cells research was confirmed by another analyst who was unaware of the survey data. We couldn’t find define another laboratory parameters as predictors of infection by BKV.